Deep groin repair procedures - Croci, Fabio; Pérez Penco, Ernesto; Cordal, Adriana (Cirugía del Uruguay, 1986)
Authors study the deep inguinal orifice in men, normal and herniated, both from the anatomic and the physiopathological and surgical point of view. Repairing procedures of same are analysed in respect of external oblique inguinal hernia. A change in the classical procedures is proposed as a valid alternative for this treatment.